Uji Kinerja Bentuk Plat Aluminium Pada Alat Pengering Pakaian Menggunakan Energi Panas Matahari Dengan Sistem Sirkulasi Alam Kapasitas Ruangan 150 M3 - Syukarni Ali; Mahyunis Mahyunis; Jufrizal Jufrizal; Jos Susilo (universitas teuku umar, 2016)
Increasing population growth affects the consume energy, it is necessary to conduct a study for product renewable energy. The biggest energy source is Sun, that can not be discharged. One of the utilization of solar energy is for heater. clothes dryer test with the use of aluminum plate as an absorbent and heat release is done by varying the shape of the surface of the different aluminum plate. The variance in the surface shape aluminum plate is used aims to determine heat numbers to be generated by the process of absorption and release of heat. The variation of the surface shape of the aluminum plate is a semi-circular shape surface, the flat shape and trapezoidal wave form. The results of the testing plate variations for clothes dryer, heat transfer rate obtained by the average value of the highest temperature of the aluminum plate is the aluminum surface a semicircle forms of 65.8oC with an average intensity of solar radiation 762,9W / m2. The result of the material jean obtained wet water content of 65.4%, the flow rate of water mass drying of 0.97 grams / minute and an average drying rate of 0.98 grams / minute with a surface area of 3391.2 cm2 semicircle. Keywords : Energy solar radiation, the surface of the aluminum plate shape